Hubungan Pengetahuan Ibu Terhadap Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Menteng Kota Palangka Raya: Correlation of Maternal Knowledge to Exclusive Breastfeeding in the Working Area of the Menteng Helath Center, Palangka Raya City - Jemmy, Jemmy; Ningsih, Fitriani; Ovany, Riska (Jurnal Surya Medika (JSM), 2023)
Breastfeeding is the first, main and best food at the beginning of the baby’s natural life. In the working area of the Menteng Health Center, Palangka Raya City, it shows that there is still a low coverage of exclusive breastfeeding in the working area of the Menteng Health Center in Palangka Raya City. There are various factors that influence exclusive breastfeeding including maternal knowledge of exclusive breastfeeding. The purpose of this study was to determine the relationship between maternal knowledge and exclusive breastfeeding in the work area of the Menteng Health Center in Palangka Raya City. This type of research is an analytical survey using a cross sectional design. The population of this study was mothers who had children aged 0-12 and the number of samplpes is 62 people. The sampling technique uses purposive sampling. Data analysis using Chi-Square. The results of this study showed there is a relationship between maternal knowledge and exclusive breastfeeding in the working area of the Menteng Health Center in Palangka Raya City (p value of: 0.000 < α: 0.05. There needs to be counseling on the importance of exclusive breastfeeding and how to properly store breast milk to the community in the working area of the Menteng Health Center, Palangka Raya City.